Bee phenology is predicted by climatic variation and functional traits. (19th August 2020) - Stemkovski, Michael; Pearse, William D.; Griffin, Sean R.; Pardee, Gabriella L.; Gibbs, Jason; Griswold, Terry; Neff, John L.; Oram, Ryan; Rightmyer, Molly G.; Sheffield, Cory S.; Wright, Karen; Inouye, Brian D.; et al.
Abstract: Climate change is shifting the environmental cues that determine the phenology of interacting species. Plant–pollinator systems may be susceptible to temporal mismatch if bees and flowering plants differ in their phenological responses to warming temperatures. While the cues that trigger flowering are well‐understood, little is known about what determines bee phenology. Using generalised additive models, we analyzed time‐series data representing 67 bee species collected over 9 years in the Colorado Rocky Mountains to perform the first community‐wide quantification of the drivers of bee phenology. Bee emergence was sensitive to climatic variation, advancing with earlier snowmelt timing, whereas later phenophases were best explained by functional traits including overwintering stage and nest location. Comparison of these findings to a long‐term flower study showed that bee phenology is less sensitive than flower phenology to climatic variation, indicating potential for reduced synchrony of flowers and pollinators under climate change. Abstract : Climate change has the potential to disrupt plant–pollinator synchrony due to different phenological responses to environmental cues. We provide the first community‐wide assessment of the drivers of bee phenology. We find that while bees time their foraging to similar environmental cues as flowers, topographic variables and species functional traits also determine phenology.